Investigation into the relationship between ethylene and sulfur assimilation in Arabidopsis thaliana and onion (Allium cepa L.) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science (with Honours) in Biochemistry at Massey University - Sanggang, Fiona Ann (Massey University, 2006)
The phytohormone ethylene (C2H4) mediates the adaptive responses of plants to various nutrient deficiencies including iron (Fe)-deficiency, phosphorus (P)-deficiency and potassium (K)-deficiency. However, evidence for the involvement this hormone in the sulfur (S) deficiency response is limited to date. In this study, the effect of C2H4 treatment on the accumulation of the S-assimilation enzymes ATP sulfurylase (ATPS). adenosine-5 -phosphosulfate-reductase (APR), O-acetylserine-(thiol)-lyase (OASTL) and sulfite reductase (SiR) was examined in A. thaliana and onion (A. cepa). To complement this, the effect of short-term S-depletion on the expression of the 12-member gene family of the C2H4 biosynthetic enzyme, l-amino-cyclopropane-l-carboxylic acid (ACC) synthase (ACS) from A. thaliana, designated AtACS1-12, was also examined. Western analyses were used to show that plants of A. thaliana pre-treated with the C2H4-signalling inhibitor 1-MCP, had elevated levels of ATPS, APR and OASTL protein in leaf tissue at all time points examined, suggesting that C2H4 has an inhibitory effect on the accumulation of these enzymes. However, SiR appeared to be under dual regulation by C2H4: under S-sufficient conditions C2H4 appears to prevent the unnecessary accumulation of SiR and conversely promote the fast accumulation of SiR under S-depleted conditions. The changes in AtACS1-12 expression in the root and leaf tissues of S-sufficient and S-depleted plants of A. thaliana were examined by RT-PCR using gene-specific, exon-spanning primers. The expression patterns of AtACS2, AtACS6 and AtACS7 were comparable regardless of S availability and may therefore be housekeeping genes. In contrast, the expression of AtACS5 in leaf, and AtACS8 and AtACS9 in roots was repressed under S-depleted conditions, although the mechanism of this repression cannot be elucidated from this study. The protein products of these closely-related genes are believed to be phosphorylated and stabilised by a CDPK whose activity may be compromised by S-depletion. The inhibition of AtACS5, AtACS8 and AtACS9 expression, and the decrease in AtACS5, AtACS8 and AtACS9 accumulation, and hence less C2H4 production, may be part of the plant adaptive response to S-depletion, as the C2H4 -mediated repression of root growth is alleviated to allow the plant to better seek out the lacking nutrient. The expression of the MPK-stabilised genes AtACS2 and AtACS6 appeared to be similar regardless of S availability, although this may merely be a consequence of the scoring method used in this study, which cannot determine whether there was any difference in the level of expression of these genes. The expression of AtACS10 and AtACS12 was repressed in S-deficient plants. Although both AtACS10 and AtACS12 isozymes posses the hallmark seven conserved regions found in the ACSes of other plant species, they are also phylogenetically related to alanine and aspartate aminotransferases, and are known to encode aspartate (AtACS10) and aromatic amino acid transaminases (AtACS12). Therefore, the apparent downregulation of these genes suggests that the downregulation of amino acid metabolism may be part of the plant adaptive response to S-depletion. The downregulation of several AtACS genes, and therefore possibly also C2H4 biosynthesis, in S-deficient plants was accompanied by an accumulation of APR protein. The increase in APR protein that also occurred in 1-MCP-treated plants indicates that C2H4 may be involved in the plant response to S-depletion, because in both cases the upregulation of the S-assimilation pathway, as manifested by the accumulation of APR protein, occurred when C2H4 biosynthesis and signalling was repressed. However, the possible role of other phytohormoes in the plant response to S-depletion cannot be excluded, as there is evidence for crosstalk between the C2H4 signalling pathway and those of auxin, abscisic acid (ABA), cytokinins and jasmonic acid (JA). Furthermore, because C2H4 has been implicated in the response of various plants to Fe-deficiency, P-deficiency, and K-deficiency, in addition to S-deficiency, it may be a regulator of the plant adaptive response to nutrient stresses in general.
Keywords: Metabolism; Plant enzymes; Molecular genetics; Plant genetic regulation; Ethylene; Sulfur; Plant gene expression; Plant proteins; Arabidopsis thaliana; Onions; Plants -- Effect of sulfur on